ANALYSIS OF STOCK INVESTMENT DECISION MAKING USING THE CAPITAL ASSET PRICING MODEL (CAPM) ON THE MNC36 INDEX: Capital Asset Pricing Model, return, risk, market return, stock beta, investment decision - Silitonga, Hery Pandapotan; Anastasia Putri, Juan; Arshandy, Eliza (Sekolah Tinggi Ilmu Ekonomi Sultan Agung, 2025)
The objective of the research conducted is to describe the return and risk of stocks in the MNC36 Index listed on the Indonesia Stock Exchange throughout 2018–2022 and to evaluate investment decisions based on undervalued and overvalued return conditions using the Capital Asset Pricing Model (CAPM) method. In this research, the method applied is descriptive analysis in both qualitative and quantitative forms. The results of the research show that: 1) There are 7 undervalued or efficient company stocks, where the individual returns are higher than expected, making these stocks worth buying before their prices rise. These stocks include: ANTM, BBCA, BBRI, BMRI, ICBP, MNCN, and PTBA. 2) There are 2 overvalued or inefficient company stocks, where the individual returns are lower than expected, making these stocks better sold before their prices drop. These stocks are: ASII and BBNI.